Electricity Supply Preferences in Europe: Evidence from Subjective Well-Being Data - Heinz Welsch; Philipp Biermann (University of Oldenburg, Department of Economics, 2013)
We use survey data for 139,517 individuals in 26 European Countries, 2002-2011, to estimate the relationship between subjective well-being (SWB) and production shares of various types of electricity generation. The estimated relationships are taken to represent preference relationships over attributes of electricity supply systems (costs, safety, environmental friendliness etc.). Controlling for a variety of individual and macro-level factors, we find that individuals' SWB varies systematically and significantly with differences in the electricity mix across countries and across time. Among other results, we find that a greater share of solar and wind power relative to nuclear power is associated with greater SWB and that the implied preference for solar and wind power over nuclear power has risen drastically after the Fukushima nuclear accident. In general, our results suggest that environmental and safety concerns are of major importance in European citizens' preference function over electricity supply structures.
Keywords: Q42; Q48; I31; 330: energy mix; preference; subjective well-being; energy transition; Fukushima; Zufriedenheit; Energieversorgung; Energiequelle; Europa